Electrophysiological mechanism of ventricular automaticity : a model foe ventricular arrythmias - Saman, Selva; Saman, Selva (MRC/UCT Cape Heart Centre, 2017)
Ventricular arrhythmias are difficult to study in man. The current experimental models are arrhythmias induced by electrical stimulation, coronary artery ligation or by subsequent reperfusion. An electrophysiological model will be useful for exploring the cellular mechanism of arrhythmias and for studying the mechanism of action of new anti-arrhythmic drugs. This project seeks to establish automaticity as a model for studying ventricular arrhythmias. Objectives 1. To review the literature on the mechanism of ventricular arrhythmias. 2. To explore ventricular automaticity induced by "reperfusion" after O₂ and substrate deprivation. 3 . To explore beta-adrenoceptor mediated ventricular automaticity. 4 . To evaluate possible new anti-arrhythmic drugs, carminomycin and ketanserin.